The association between serum vitamin A and NAFLD among US adults varied in different BMI groups: a cross-sectional study. Issue 2 (2nd November 2022) - Zhang, Kaiwen; Nulali, Jiayida; Zhang, Caoxu; Chen, Yingchao; Cheng, Jing; Shi, Xiaye; Zhu, Chunfang; Lu, Yingli; Wang, Ningjian; Han, Bing
Abstract : The association between serum vitamin A (VA) and non-alcoholic fatty liver disease (NAFLD) has not been adequately studied. Abstract : Background and aims : The association between serum vitamin A (VA) and non-alcoholic fatty liver disease (NAFLD) has not been adequately studied. This study aimed to evaluate the association between them in different BMI groups among US adults. Methods : A cross-sectional study was performed using the 2017–2018 National Health and Nutrition Examination Survey (NHANES) datasets ( N = 4.723). Linear/logistic regression, interaction effect and mediation analyses were adopted to analyze the association. Results : NAFLD tended to be more prevalent in adults in the middle and high tertiles of serum VA than in those in the low tertile of serum VA (OR [95% CI], 1.17 [0.94, 1.45] and 1.43 [1.16, 1.75]). In the sensitivity analysis, subjects in the middle or high tertile of serum VA had 10% (OR, 1.10 [0.88, 1.39] and 31% (OR, 1.31 [1.09, 1.58]) higher odds of NAFLD than those in the low tertile of serum VA. In the normal weight group, higher serum VA was associated with 125% and 333% higher odds of NAFLD in the middle and high tertiles, respectively, (OR, 2.25 [1.46, 3.48] and 4.33 [2.43, 7.69]) compared with the low tertile serum VA group. However, serum VA and NAFLD were not significantly associated with the obese group. Among different BMI groups (<30 compared with ≥30), serum triglycerides and insulin resistance mediated the association between VA and NAFLD in adults to varying degrees. Conclusions : In the weighted survey, serum VA was positively associated with the degree of NAFLD, especially in the non-obese population.